THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE ON POLICE EMPLOYEES' PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AS A VARIABLE INTERVENING IN JAMBI REGIONAL POLICE - Permatasari, Wulan Dyah; Adriani, Zulfina; Ratnawati, Ratnawati (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2025)
This study aims to determine the knowledge of Transformational Leadership Style on Police Officer Performance with Organizational Commitment as an intervening variable at the Jambi Regional Police Human Resources Bureau. This study uses a quantitative approach, the data collection technique is through the distribution of questionnaires to 75 respondents. The hypothesis test is carried out through the use of descriptive analysis methods and data processing through the SmartPLS 4 application. The research findings show that Transformational Leadership Style has a positive and significant effect on Police Officer Performance, Transformational Leadership Style has a positive and significant effect on Organizational Commitment and Organizational Commitment has a positive and significant effect on Police Officer Performance